Postprandial triglyceride-rich lipoproteins as predictors of carotid atherosclerosis in individuals with normal fasting lipid profiles: a prospective follow-up study - Hou, Yilin; Tian, Peipei; Song, Guangyao; Song, An; Liu, Dandan; Wang, Zhimin; Shi, Yihe; Tang, Yale; Wang, Xiaoyu; Li, Luxuan; Ren, Luping (Frontiers in Endocrinology, 2025)
BackgroundCarotid atherosclerosis (CAS), a key precipitator of cardiovascular incidents, is linked to postprandial triglyceride-rich lipoproteins (TRL), as reflected by elevated triglycerides (TG) and remnant cholesterol (RC). This study explores the oral fat tolerance test (OFTT) for its predictive value in CAS, using postprandial TRL levels as a diagnostic biomarker.MethodsA total of 107 volunteers with normal fasting lipid profiles and no CAS at baseline were included. They received an OFTT after consuming a meal containing 60% fat (1500 kcal). Serum lipid profiles were monitored at fasting and 2, 4, 6, 8, and 10 h postprandially. The participants were categorized into postprandial normotriglyceridemia and postprandial hypertriglyceridemia groups based on their postprandial TG levels. After a 6-year follow-up, fasting lipid profiles and CAS status were reassessed. The baseline fasting and postprandial lipid levels in the CAS and non-CAS groups were compared. Repeated-measures analysis of variance was used to analyze the postprandial lipid profiles across different groups. Logistic regression models were constructed to assess the effects of postprandial TG and RC levels on CAS incidence.ResultsThe incidence of CAS in the postprandial hypertriglyceridemia group was 66.0%, which was significantly higher than the 13.3% observed in the postprandial normotriglyceridemia group (P < 0.001). In the CAS group, postprandial TG and RC levels peaked 4 h after a high-fat meal and did not return to fasting levels, even after 10 h. The levels of 4h-postprandial TG (TG4h), maximum postprandial TG (TGmax), 4h-postprandial RC (RC4h), and maximum postprandial RC (RCmax) were significantly higher in the CAS group than in the non-CAS group (P < 0.05). At baseline, TG4h (P < 0.001), TGmax (P = 0.006), RC4h (P < 0.001), and RCmax (P = 0.003) were statistically significant predictors of CAS, whereas fasting TG (P = 0.200) and fasting RC (P = 0.200) were not significantly associated with CAS.ConclusionThe standardized OFTT has predictive value for CAS, and elevated TRL levels after a high-fat meal in individuals with normal fasting lipid profiles may serve as an early marker for CAS.